Predicting Interfacial Characteristics during Powder Bed Fusion Process - Pal, Prabhakar (My University, 2022)
Powder bed fusion (PBF) is a metal additive manufacturing process that is increasingly used in the aerospace and medical industry to build complex parts directly from computer-aided design. Due to the presence of large temperature gradients and rapid cooling rates during the processing, the PBF process is assumed to follow a rapid solidification processing route. However, the extent of deviation of the solid-liquid interface from equilibrium as a function of processing conditions has not been studied in detail for the PBF process. In this thesis, a numerical model is developed to study the interfacial characteristics as a function of processing conditions to characterize if the PBF process exhibits rapid solidification or not. The model is based on the work of Hunt et al. [1, 2, 3] and is capable of simulating cellular and dendritic growth at both low and high interface velocities. The developed model accounts for the various undercooling such as constitutional and curvature undercooling, the variation of the liquidus temperature with composition, and the partition coefficient and diffusion coefficient with temperature. Moreover, the variation of the partition coefficient and the liquidus slope with the growth velocity has also been considered in the developed model. The model is used to predict the range of primary cellular/dendritic spacing for a given set of input parameters. In addition to this, the tip undercooling, tip Péclet number and spacing Péclet numbers have also been estimated using the model to quantify the extent of deviation of the solid-liquid interface from equilibrium. A good qualitative agreement between the predicted values from the numerical model and the analytical KGT model is achieved. This new model can be used to understand the relationship between the processing conditions, material system and interfacial characteristics during the PBF process, and thus improve microstructural development during PBF processing.
Keywords: Powder Bed Fusion Process; Rapid Solidification; Cells; Dendrites